O ensino de leitura em língua espanhola em uma perspectiva enunciativo-discursiva - Ormond, Rosária Cristina da Silva (2015)
Abstract: This research aims presenting conceptual and didactic proposals to work with the reading, at the public school environment, according to the needs established by the current social practices. The questions which guided this investigation were: 1) What are the conceptions of language and reading that the language teachers, subjects of this research, have? 2) What is possible to do for reversing probable misadjustments between the construction of the reading skills and the current needs? In order to answer the previous questions, it was done observations in ten classes of Spanish for a foreign language in a state school in the city of Cuiabá, where it was applied a questionnaire to five teachers who teach Spanish at public schools. This research is inscribed in Applied Linguistics scope taking as theoretical basis the French Approach of Discourse Analysis. Data analysis suggests that the teachers’ conceptions of reading are seen sometimes as a decoding and as an interaction between the reader and the text. At the end of this thesis, it was proposed a continuing formation course aimed at explaining the theoretical principles of enunciative-discursive approach, as well as, materialize them on educational proposals functioning in reading teaching in Spanish Language, causing changes in pedagogical practices of teachers Spanish for a foreign language who teach at the public school system.